2021
DOI: 10.3390/ph14050428
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoids from the Genus Euphorbia: Isolation, Structure, Pharmacological Activities and Structure–Activity Relationships

Abstract: Plants of the genus Euphorbia are widely distributed across temperate, tropical and subtropical regions of South America, Asia and Africa with established Ayurvedic, Chinese and Malay ethnomedical records. The present review reports the isolation, occurrence, phytochemistry, biological properties, therapeutic potential and structure–activity relationship of Euphorbia flavonoids for the period covering 2000–2020, while identifying potential areas for future studies aimed at development of new therapeutic agents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 120 publications
(162 reference statements)
0
25
0
Order By: Relevance
“…The effect of antimicrobial activities was particularly relevant to the conversion of highly hydrophilic groups and steric hindrance of reactive sites [26]. Magozwi et al revealed that methylation of the hydroxyl groups on C-3 or C-7 reduced the antimicrobial activity of flavonoids [27]. Research on quercetin indicated that the loss of a hydroxyl group at C-3 was associated with low activity [27].…”
Section: Discussionmentioning
confidence: 99%
“…The effect of antimicrobial activities was particularly relevant to the conversion of highly hydrophilic groups and steric hindrance of reactive sites [26]. Magozwi et al revealed that methylation of the hydroxyl groups on C-3 or C-7 reduced the antimicrobial activity of flavonoids [27]. Research on quercetin indicated that the loss of a hydroxyl group at C-3 was associated with low activity [27].…”
Section: Discussionmentioning
confidence: 99%
“…Much research has been carried out in order to highlight the phytochemical profile of different Euphorbia spp. This has allowed the identification of numerous classes of secondary metabolites with marked health properties, including multi-drug resistance modulatory activity, antiproliferative, cytotoxic, antiviral, antimicrobial, antioxidant, and anti-inflammatory activity [ 5 , 9 , 13 , 14 , 17 , 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among these compounds, the most representative are sesquiterpenes, diterpenes, triterpenes, steroids, cerebrosides, phenolic compounds, tannins, and coumarins [ 5 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations